EUROPEANIZATION OF THE UKRAINIAN SYSTEM OF HIGHER PEDAGOGICAL EDUCATION THROUGH THE IMPROVEMENT OF UNDERGRADUATES’ FOREIGN LANGUAGE COMMUNICATIVE SKILLS - Gromov, Yevhen; Kolomiiets, Alla; Kolomiiets, Dmytro; Mazaikina, Iryna; Nalyvaiko, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article is devoted to the problem of improvement of the foreign language communicative skills of future Masters of Pedagogical Science. Special attention has been given to the issue of gradual introduction into the educational process the practice of teaching undergraduate students some academic disciplines in the English language. The authors share their successful experience of teaching undergraduates of the Physical-Mathematical and the Informational-Technological specialties general-academic disciplines in English. This practice is considered one of the effective ways to increase the students’ foreign language competence. On the example of a general-academic discipline «Methodology and Principles of Scientific Research» the authors prove the urgency and expediency of teaching certain subjects in the foreign languages to the applicants of the Master's Degree in Pedagogical Science. The purpose of this article is to demonstrate the importance of such practice and to show that teaching some general subjects in English can become a significant factor of improvement of the students’ foreign competence, which in turn contributes to the integration of the Ukrainian scientific-pedagogical community into the European academic community.